7 ate 9 the untold story - Lazar, Tara.; MacDonald, Ross 1957- (Los Angeles Disney, Hyperion, 2017)
When 7 is accused of eating 9, worried 6 hires a detective to investigate.
School Library Journal starred, May 2017
Publisher's Weekly, March 2017
New York Times, July 2017
Horn Book, May 2017
Kirkus Review, March 2017
1.5.
Keywords: Numbers -- Fiction; Counting -- Fiction; Detective and mystery fiction; Picture books